Comparative study of the place's usage and its types in the novel's critique (Case study: Hakayeh Bohar Hana Mina and Ahl-Gharq Monroe Psychoanol) - Mahmoud Reza Tawakoli Mohammadi; Masume Siyami (ادبیات تطبیقی, 2020)
1. Introduction Place is one of the main elements of the story frame that contributes to the advancement of events and their understanding. The role of place in contemporary novels is very prominent and writers have always paid special attention to this important element and used it with specific skill to express their goals. "Henna Mina" and "Moniro RavaniPour" are among the writers who have paid special attention to place and have made their own goals in the writing of the novel based on this important element; therefore, the study of place in novel can help us in this regard.   2. Methodology The present study is based on descriptive-analytical method and based on the American School of Comparative Literature, based on the application of the place and its types, the comparative study of two novels of the "bahhar" and "Ahle-Gharq" stories has been studied.   3. Discussion  The place and its types play an important role in both the work as an active and influential element in presenting the history of the presence of aliens in the lands. In describing places with superstition and mythology and the use of symbolic maps, both authors have better reflected and influenced the hostilities and attacks of foreigners and how they entered. Both authors have used real names in the use of place names to be effective in describing the events of their homeland and the problems of foreign entry. The forced confinement of the prison in the novel "hekayah bahar" plays a very important role in showing the perseverance and solidarity of the Syrian people against the occupiers, but the prison in the novel "Ahl-e Gharg" mostly expresses the suffering and torture of innocent prisoners who are unaware of society. The optional closed space of the house has played an important role in providing themes such as poverty and the lack of proper conditions and increasing class distance due to the existence of colonialists. The open sea has themes such as the grief and destruction of men against the onslaught of enemies by sea. The transfer location plays an important role in how enemies move into other countries. Finally, it should be noted that the place, as an influential element, plays a prominent role in the two novels, so that it can be considered as the main element and the middle pillar of the foundation of these two novels.     4. Conclusion Findings of the research show that despite the many differences in the use of different types of places, the two authors have used the open sea for the most purposes in expressing their goals. Keywords Comparative Literature, Place, Colonial, Hana Mina, Moniro ravanipor.